Import Demand Function of Rice in Indonesia - Prasetyo, Agung Dwi; Anindita, Ratya (HABITAT, 2016)
To fulfil the need of rice is to increase the domestic production, which is the one of the governmentâs policy. However, by increasing the population, the demand of rice will also increase and the effort of increase the domestic productivity cannot supply the need of domestic rice. So, to cover the shortage the government makes decision to import rice from other countries. Gross Domestic Product (GDP) also increased after monetary crisis in 1998. In the fact of the import of rice is occurred when the statistical data showed that the supply of rice in Indonesia is surplus. The aim of this research is necessary to study the factors which influence the import of rice in Indonesia. The analysis method used is multiple linear regression analysis model with Error Correction Model (ECM). Based on the research proven that partially or jointly the gross domestic product, the consumption, the price of rice in world market are influence significantly toward the import of rice in Indonesia.